Epigallocatechin‐3‐Gallate (EGCG) Reduces Rotenone Effect on Stallion Sperm–Zona Pellucida Heterologous Binding. Issue 6 (20th October 2015) - Plaza Dávila, M; Bucci, D; Galeati, G; Peña, FJ; Mari, G; Giaretta, E; Tamanini, C; Spinaci, M
Contents: Stallion spermatozoa are highly dependent on oxidative phosphorylation for ATP production to achieve normal sperm function and to fuel the motility. The aim of this study was to evaluate the response of equine sperm under capacitating conditions to the inhibition of mitochondrial complex I by rotenone and to test whether epigallocatechin‐3‐gallate (EGCG), a natural polyphenol component of green tea, could counteract this effect. After 2‐h incubation of stallion spermatozoa in modified Tyrode's medium, rotenone (100 nm, 500 nm and 5 μm ) and EGCG (10, 20 and 60 μm ), alone or in combination, did not induce any significant difference on the percentage of viable cells, live sperm with active mitochondria and spermatozoa with intact acrosome. The inhibition of complex I of mitochondrial respiratory chain of stallion sperm with rotenone exerted a negative effect on heterologous ZP binding ability. EGCG at the concentrations of 10 and 20 μm (but not of 60 μm ) induced a significant increase in the number of sperm bound to the ZP compared with that for control. Moreover, when stallion sperm were treated with rotenone 100 nm, the presence of EGCG at all the concentrations tested (10, 20 and 60 μm ) significantly increased the number of sperm bound to the ZP up to control levels, suggesting that this green tea polyphenol is able to reduce the toxicity of rotenone.